PEMBUATAN MEDIA PEMBELAJARAN PENGENALAN TATA SURYA DAN EXOPLANET DENGAN MENGGUNAKAN UNITY UNTUK SEKOLAH MENENGAH PERTAMA - Wamiliana Wamiliana; Dian Kurniasari; Jevri Setia Nugraha (Universitas Lampung, 2013)
Technology development currently making human life be more practical. There are many ways to use technology like for entertainment, business, and education. The use of technology in education is still not optimal so that the educational process is still using the old system where students listen and the teachers explain. One of the education technology is to do the process of learning using the multimedia interactive. Subjects about the solar system is one of the subjects taught in junior high school, but the topics about exoplanets or planets which are outside the solar system are seldom given by the teacher. Most junior high school used the interactive multimedia to help learning process but it is still 2D-based and only gave topics about the solar system. Therefore, in this paper we discused about the design and development of an interactive multimedia which contains topics about solar system and exoplanets with animated interactive multimedia in 3D-based. This application will be more attractive, and the users can use it interactively.Keywords: 3D-based interactive multimedia, education, solar system and exoplanet, technology development.